If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 4 + 8 + 2x = 3(x + 5) Reorder the terms: 4 + 8 + 4x + 2x = 3(x + 5) Combine like terms: 4 + 8 = 12 12 + 4x + 2x = 3(x + 5) Combine like terms: 4x + 2x = 6x 12 + 6x = 3(x + 5) Reorder the terms: 12 + 6x = 3(5 + x) 12 + 6x = (5 * 3 + x * 3) 12 + 6x = (15 + 3x) Solving 12 + 6x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 6x + -3x = 15 + 3x + -3x Combine like terms: 6x + -3x = 3x 12 + 3x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + 3x = 15 + 0 12 + 3x = 15 Add '-12' to each side of the equation. 12 + -12 + 3x = 15 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 15 + -12 3x = 15 + -12 Combine like terms: 15 + -12 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 3u^2+17u+24=0 | | 4x+6(x+2)=35 | | (5x-3)/9=-2 | | 2/3x5/6x14x18 | | -8(3x+1)-4=11 | | 3000(x+100)=2000(x-100) | | -4-8y=35 | | 2(x-5)(x+4)=0 | | 2x-5+8x=7-4x-12 | | 2(14+2x)=8(2+x) | | 2•1/3•3.14•25•25•25 | | 2u^2+15u+28=0 | | 4x+9x-34=68-4x | | -14=-3x | | 3x+7=5x+1-x | | 10/12*1/4= | | y=log^4(3x+11)-5 | | 6.1-0.25(x-8)=0.7x+0.3(x-3) | | 8y+9=6y+14 | | 4(.5-.25y)+y=2 | | 5e^2x=13 | | 12/x^2-4 | | 6x-4+2=3a+1 | | 5-m=113 | | 7-2y=1ty | | -7/10:21/20 | | (3/5)x=7^1-x | | -7/10/21/20 | | 2(w+1)=16 | | 18=19-8d | | 4z+7=34-5z | | 5(x+4)+2=3(x+7)+5 |